Analisis Tingkat Kesehatan Bank dengan Metode RGEC (Risk Profile, Good Corporate Governance, Earning, and Capital) pada PT. Bank Panin Dubai Syariah Tbk., Periode 2019-2023 - Selvina Sandini; Anwar Ramli; Anwar Anwar (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to assess the financial health of PT. Bank Panin Dubai Syariah Tbk using the RGEC method. The object of this research is PT. Bank Panin Dubai Syariah Tbk. The research adopts a descriptive quantitative approach. The population in this study consists of the financial reports of PT. Bank Panin Dubai Syariah Tbk, while the sample includes financial reports from 2019 to 2023. The data used in this study is secondary data. The evaluation results indicate that, based on the RGEC method, the overall financial health of PT. Bank Panin Dubai Syariah Tbk for the 2019–2023 period received a composite rating of 3, with a composite score of 70.67%, indicating a